PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS VIII2 SMP NEGERI 3 TANAH PUTIH KABUPATEN ROKAN HILIR - Indrawati, Henny; Haryana, Gani; ', Lisdarika (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem this research is the students achievement of social studies SMP N 3 Tanah Putih fourth graderes still low with an average value of 63.93 and minimum completenness criteria (KKM) social studiesis 75. Between students, amounting to 28 people only 12 students who achieve classical KKM with 42.86%. This research is classroom action research (CAR), which aims to improve the student achievement of social studies class VIII2 at SMP N 3 Tanah Putih with implementation cooperative learning model type Two Stay Two Stray (TSTS). Formulation of the problem : is the implementation of cooperative learning model type Two Stay Two Stray (TSTS) can improve students achievement of social studies at SMP N 3 Tanah Putih. The research was conducted on January 25, 2016 ‘to February 15, 2016 by 2 cycles. Subjects werw students of SMP N 3 Tanah Putih, totaling 28 people who use the data source. The data collection instruments in this skription is a teacher and students activities sheets and students achievement. This skription presents the results obtained each day before the action an improve in base score cycle with the average being 63.93. In the first cycle improve an average of 81.79 and an improve in the second with an average 90.00. Activities of the teacher in the learning process in cycle of 70.83% and the second meeting improve to 91.67%. In the third cycle of the first meeting and the second meeting improve.Keywords: cooperative learning model type Two Stay Two Stray and Learning Outcomes